ANALISIS PENGGUNAAN APLIKASI ASABRI MOBILE TERHADAP PENINGKATAN CORPORATE VALUE PADA PT ASABRI (PERSERO) KANTOR CABANG BANDUNG - Citra Ayu Agustin; Chandra Hendriyani; Agus Garnida (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
Digital tarsformation has become a strategic necessity for State Owned Enterprises (SOS) in enhancing corporate value and service quality to stakeholders. This study aims to analyze the implementation of the ASABRI Mobile application in improving the corporate value of PT ASABRI (Persero). Bandung Branch Office, through the lens of the SOE core value known as AKHLAK an acronym for Amanah (Trustworthy), Kompeten (Competent), Harmonis (Harmonious), loyal (Loyal), Adaptif (Adaptive), and Kolaboratif (Collaborative). The research uses a qualitative approach, incorporating direct observation and secondary data analysis from relevant literature and user reviews on digital platforms. Findigs indicate that although the ASABRI Mobile application has been downloaded over one million times, user satisfactions remains low, with 66% of respondent expressing dissatisfaction due to technical issues such and OTP delays, login failures, unresponsive features, and PIN memorability problems. These challenges reflect the suboptimal internalization of AKHLAK values in the digital service process. The misalignment between ideal corporate values and digital implementation risk weakening public perception and diminishing long term corporate value. This study recommends systematic improvements, including the optimization of digital infrastructure, implementation of Multi Factor Authentication (MFA), and the enhancement of technical competencies among human resources. Consequently, digitalization can serve as a catalyst for sustainable enhancement of corporate value within PT ASABRI (Persero).